Nested Hexagrams and Circles

Geometry Level 4

For each positive integer n n , let A p ( n ) A_{p}(n) be the area of the hexagram inscribed in a circle of area A c ( n ) A_{c}(n) and A c ( n + 1 ) A_{c}(n + 1) be the area of the circle inscribed in the hexagram of area A p ( n ) A_{p}(n) . Let A c = n = 1 A c ( n ) A_{c} = \sum_{n = 1}^{\infty} A_{c}(n) and A p = n = 1 A p ( n ) A_{p} = \sum_{n = 1}^{\infty} A_{p}(n) .

If A c A p A c ( 1 ) 2 = 1 π ( a b ) b a \dfrac{A_{c} A_{p}}{A_{c}(1)^2} = \dfrac{1}{\pi}\left(\dfrac{a}{b}\right)^{b}\sqrt{a} , where a a and b b are coprime positive integers, find a + b a + b .

:


The answer is 5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Jan 28, 2019

2 h 1 r 1 = tan ( 3 0 ) = 1 3 h 1 = 1 2 3 r 1 \dfrac{2h_{1}}{r_{1}} = \tan(30^\circ) = \dfrac{1}{\sqrt{3}} \implies h_{1} = \dfrac{1}{2\sqrt{3}}r_{1} and r 1 2 = r 2 cos ( 3 0 ) = 3 2 r 2 r 2 = 1 3 r 1 \dfrac{r_{1}}{2} = r_{2}\cos(30^\circ) = \dfrac{\sqrt{3}}{2}r_{2} \implies r_{2} = \dfrac{1}{\sqrt{3}}r_{1} .

h 2 = 1 3 r 2 = 1 2 3 ( 1 3 ) r 1 , r 3 = 1 3 r 2 = ( 1 3 ) 2 r 1 , h 3 = 1 2 3 r 3 = 1 2 3 ( 1 3 ) 2 r 1 \implies h_{2} = \dfrac{1}{\sqrt{3}}r_{2} = \dfrac{1}{2\sqrt{3}}(\dfrac{1}{\sqrt{3}})r_{1}, \:\ r_{3} = \dfrac{1}{\sqrt{3}}r_{2} = (\dfrac{1}{\sqrt{3}})^2r_{1}, \:\ h_{3} = \dfrac{1}{2\sqrt{3}}r_{3} = \dfrac{1}{2\sqrt{3}}(\dfrac{1}{\sqrt{3}})^2r_{1}

In General:

r n = ( 1 3 ) n 1 r 1 r_{n} = (\dfrac{1}{\sqrt{3}})^{n - 1}r_{1} and h n = 1 2 3 ( 1 3 ) n 1 r 1 h_{n} = \dfrac{1}{2\sqrt{3}}(\dfrac{1}{\sqrt{3}})^{n - 1}r_{1}

A c ( n ) = ( 1 3 ) n 1 A c ( 1 ) \implies A_{c}(n) = (\dfrac{1}{3})^{n - 1}A_{c}(1) and A p ( n ) = 3 π ( 1 3 ) n 1 A c ( 1 ) A_{p}(n) = \dfrac{\sqrt{3}}{\pi}(\dfrac{1}{3})^{n - 1}A_{c}(1)

A c = 3 2 A c ( 1 ) \implies A_{c} = \dfrac{3}{2}A_{c}(1) and A p = 3 3 2 π A c ( 1 ) A_{p} = \dfrac{3\sqrt{3}}{2\pi}A_{c}(1)

A c A p A c ( 1 ) 2 = 1 π ( 3 2 ) 2 3 = 1 π ( a b ) b a a + b = 5 \implies \dfrac{A_{c} * A_{p}}{A_{c}(1)^2} = \dfrac{1}{\pi}(\dfrac{3}{2})^2\sqrt{3} = \dfrac{1}{\pi}(\dfrac{a}{b})^{b}\sqrt{a} \implies a + b = \boxed{5} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...